Peningkatan Keterampilan Membaca Pemahaman Peserta Didik Menggunakan Model Cooperative Learning Tipe Jigsaw di Kelas V SD Negeri 03 Pakan Kurai Kota Bukittinggi - Rafika, Rafika; Suriani, Ari (Lembaga Yasin AlSys, 2024)
Cooperative Learning Model type Jigsaw is a learning model that can be used in the learning process to improve the reading skills of the student's understanding. The background of this study is poor reading skills, learning processes that are still centered on the teacher, students who have difficulty understanding the reading text and identifying the key ideas or basic ideas as well as important details contained in the text they read. The study aims to describe improved reading skills and understanding of the student using the Cooperative Learning model of the Jigsaw type. The research was carried out at the SDN 03 Pakan Kurai City of Bukittinggi. This type of research is class action research that consists of four stages of planning, implementation, observation, and reflection. This research uses both qualitative and quantitative approaches. The research was carried out in two cycles, Cycle I consisting of two meetings and Cycle II consisted of one meeting. Subject of the research is the student of V SD State 03 Pakan Kurai City Bukittinggi. This study showed that there was an improvement in the reading skills of learners using the Cooperative Learning model of Jigsaw. Thus, the cooperative learning model of jigsaw can be an effective option for enhancing the learning skills of students.